KiDS-SQuaD: The KiDS Strongly lensed Quasar Detection project. Issue 1 (19th July 2018) - Spiniello, C; Agnello, A; Napolitano, N R; Sergeyev, A V; Getman, F I; Tortora, C; Spavone, M; Bilicki, M; Buddelmeijer, H; Koopmans, L V E; Kuijken, K; Vernardos, G; et al.
ABSTRACT: New methods have recently been developed to search for strong gravitational lenses, in particular lensed quasars, in wide-field imaging surveys. Here, we compare the performance of three different, morphology- and photometry-based methods to find lens candidates within the Kilo-Degree Survey (KiDS) DR3 footprint (440 deg 2 ). The three methods are: i) a multiplet detection in KiDS-DR3 and/or Gaia-DR1, ii) direct modelling of KiDS cutouts, and iii) positional offsets between different surveys (KiDS-versus-Gaia, Gaia-versus-2MASS), with purpose-built astrometric recalibrations. The first benchmark for the methods has been set by the recovery of known lenses. We are able to recover seven out of 10 known lenses and pairs of quasars observed in the KiDS DR3 footprint, or eight out of 10 with improved selection criteria and looser colour pre-selection. This success rate reflects the combination of all methods together, which, taken individually, performed significantly worse (four lenses each). One novelty of our analysis is that the comparison of the performances of the different methods has revealed the strengths and weaknesses of the approaches and, most of all, the complementarity. We finally provide a list of high-grade candidates found by one or more methods, awaiting spectroscopic follow-up for confirmation. Of these, KiDS 1042+0023 is, to our knowledge, the first confirmed lensed quasar from KiDS, exhibiting two quasar spectra at the same source redshift at either sides of a red galaxy, with uniform flux-ratio f ≈ 1.25 over the wavelength range 0.45 μ mλ 0.75 μ m.